Utility of ultrasound as a “cognitive aid” for the managemet of awake fibre optic intubation - Shafiq, Faraz; Baig, Umair Aftab (Journal of the Pakistan Medical Association, 2025)
Dear Editor, We are writing this letter to highlight the utility of ultrasound as a cognitive aid for awake fiberoptic intubation. Securing the airway and maintaining its patency is a crucial role for anaesthesiologists. Failure to secure the airway can lead to a cascade of complications, including hypoxia, irreversible brain injury, and death. Effective use of available cognitive aids enhances the performance by reducing errors, improving confidence and related outcomes 1. Various devices are now in practice to assist in securing difficult airways by providing better visualization of airway anatomy compared to traditional direct laryngoscopy. Among them, awake fiberoptic tracheal intubation has been the gold standard for managing anticipated difficult airways2. We present the case of young male diagnosed with squamous cell carcinoma of the tongue, planned for elective tracheostomy. The patient had no other known comorbid condition. An airway examination revealed a limited mouth opening . A CT scan indicated a poorly differentiated mass of the tongue with tumor thrombus in the superior vena cava and pulmonary embolus affecting the right main pulmonary artery and its segmental branches. The tumor had also involved nodes in the right supraclavicular region and extended to the right anterior chest wall, causing marked tracheal displacement to the left side as shown in Figure 1. The anesthesia team was consulted for airway management before tracheostomy. Due to the extreme deviation of the trachea, it was challenging for the surgeon to perform tracheostomy without securing the airway with an endotracheal tube. Considering the aniticipated difficulty, awake fiberoptic intubation was planned, under routine ASA specified monitoring and ENT team on stand by in operating room. Local anaesthetic spray was administered via upper airway through nasal cavity and limited oral access. Most important aspect of procedure was to block recurrent laryngeal nerve to add comfort while using fibre scope and to add comfort to the procedure 3. As anatomy of neck was absolutely distorted, Ultrasound guidance was really helpful for locating the tracheal rings, which were shifted to extreme left up to the level of midclavicular line. A recurrent laryngeal nerve block was performed through a transtracheal approach using ultrasound.This was acheived by injecting 3 mL of 2% lidocaine through the transtracheal approach. An endotracheal tube of 7.0 mm was passed , confirmed with endtidal carbondioxide and secured. —Continue